Magnesium Reduces Hepatic Lipid Accumulation in Yellow Catfish (Pelteobagrus fulvidraco) and Modulates Lipogenesis and Lipolysis via PPARA, JAK-STAT, and AMPK Pathways in Hepatocytes. Issue 6 (19th April 2017) - Wei, Chuan-Chuan; Wu, Kun; Gao, Yan; Zhang, Li-Han; Li, Dan-Dan; Luo, Zhi
Abstract: Background: Magnesium influences hepatic lipid deposition in vertebrates, but the underlying mechanism is unknown. Objective: We used yellow catfish and their isolated hepatocytes to test the hypothesis that magnesium influences lipid deposition by modulating lipogenesis and lipolysis. Methods: Juvenile yellow catfish (mean ± SEM weight: 3.43 ± 0.02 g, 3 mo old, mixed sex) were fed a 0.14- (low), 0.87- (intermediate) or 2.11- (high) g Mg/kg diet for 56 d. Primary hepatocytes were incubated for 48 h in control or MgSO4 -containing medium with or without 2-h pretreatment with an inhibitor (AG490, GW6471, or Compound C). Growth performance, cell viability, triglyceride (TG) concentrations, and expression of enzymes and genes involved in lipid metabolism were measured. Results: Compared with fish fed low magnesium, those fed intermediate or high magnesium had lower hepatic lipids (18%, 22%) and 6-phosphogluconate dehydrogenase (6PGD; 3.7%, 3.8%) and malic enzyme (ME; 35%, 48%) activities and greater mRNA levels of the lipolytic genes adipose triacylglyceride lipase ( atgl ; 82% and 1.7-fold) and peroxisome proliferator-activated receptor ( ppara ; 18% and 1.0-fold), respectively ( P < 0.05). Relative mRNA levels of AMP-activated protein kinase ( ampk ) a1, ampka2, ampkb1, ampkb2, ampkg1a, ampkg1b, Janus kinase (jak) 2a, jak2b, and signal transducers and activators of transcription ( stat ) 3 in fish fed high magnesium were higher (24% to 3.1-fold, P < 0.05) than in those fed low or intermediate magnesium. Compared with cells incubated with MgSO4 alone, those incubated with MgSO4 and pretreated with AG490, GW6471, or Compound C had greater TG concentrations (42%, 31%, or 56%), g6pd (98%, 59%, or 51%), 6pgd (68%, 73%, or 32%) mRNA expression, and activities of G6PD (35%, 45%, or 16%) and ME (1.5-fold, 1.3-fold, or 13%), and reduced upregulation (61%, 25%, or 45%) of the lipolytic gene, atgl ( P < 0.05). Conclusions: Magnesium reduced hepatic lipid accumulation in yellow catfish and the variation might be attributed to inhibited lipogenesis and increased lipolysis. PPARA, JAK-STAT, and AMPK pathways mediated the magnesium-induced changes in lipid deposition and metabolism. These results offer new insight into magnesium nutrition in vertebrates.